2021
DOI: 10.1101/2021.08.24.457591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-associated microbial diversity in New Zealand cicadas uncovers elevational structure and replacement of obligate bacterial endosymbionts byOphiocordycepsfungal pathogens

Abstract: Host-microbe interactions influence eukaryotic evolution, particularly in the sap-sucking insects that often rely on obligate microbial symbionts to provision deficient nutrients in their diets. Cicadas (Hemiptera: Auchenorrhyncha: Cicadidae) specialize on xylem fluid and derive many essential amino acids and vitamins from intracellular bacteria or fungi (Hodgkinia, Sulcia, and Ophiocordyceps) that are propagated via transmission from mothers to offspring. Despite the beneficial role of these symbionts in nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
1
0
0
Order By: Relevance
“…We also found that its partner obligate endosymbiont Sulcia dominated our gut microbiome samples (Figs. 3 E, 5 B), supporting results found for cicadas in China and New Zealand 24 , 48 .…”
Section: Discussionsupporting
confidence: 82%
“…We also found that its partner obligate endosymbiont Sulcia dominated our gut microbiome samples (Figs. 3 E, 5 B), supporting results found for cicadas in China and New Zealand 24 , 48 .…”
Section: Discussionsupporting
confidence: 82%